HUBUNGAN DAYA LEDAK OTOT TUNGKAI DAN KOORDINASI MATA TANGAN DENGAN HASIL MEDIUM SHOOT TIM BASKET PUTRA SMA N 1 RENGAT - Dandy Novrandy Arvi; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research was conducted with the aim of finding out more about the relationship between leg muscles explosion and hand eye coordination with medium shoot results of men’s basketball team at SMAN 1 Rengat. The problem found in this research is team play of SMAN 1 Rengat is not optimal in shooting with a jump shoot that make only a few balls can entrance into the opponent’s ring and add points. This research was conducted from August to December 2020 in the field of SMAN 1 Rengat Jalan Sultan Ibrahim. Population in this research is basketball team of SMAN 1 Rengat, while the sample technique used is sample research which is use half of the population. Based on the research, the conclusion is: : there is a strong relationship between leg muscles explosion with medium shoot, which is rtab at a significant level a (0.05) = 0.576 means rcount (0.834)> rtab (0.576), there is a very strong relationship between hand eye coordination with medium shoot, which is rtab at a significant level a (0.05) = 0.576 means rcount (0.608)> rtab (0.576), there is a very strong relationship between leg muscles explosion and hand eye coordination with medium shoot result of men's basketball team at SMA Negeri 1 Rengat, , which is rtab at a significant level a (0.05) = 0.576 means rcount (0.836)> rtab (0.576).Keywords: Leg Muscles Explosion, Hand Eye Coordination, Medium Shoot.